Physical characteristics and performance in change of direction tasks: A brief review and training considerations - Bourgeois, F. A.; McGuigan, M. R.; Gill, N. D.; Gamble, P. (Journal of Australian Strength and Conditioning, 2017)
Change of direction (COD) ability is considered to be critical for a number of sports, with respect to both assessment and training. This review examined factors that may influence performance in COD tasks, including underpinning physical qualities and physiological capabilities. A web-based search using PubMED, SPORTDiscus, ScienceDirect, and Google Scholar identified a total of 197 articles using the keywords change of direction performance, change of direction ability, agility, pre-planned tasks, athletic performance, and multidirectional sprinting. Due to the complexity and multifactorial nature of COD ability there is a need for both established assessment protocols and novel sport-specific measures. Examples of recommended established protocols are high-velocity entry COD tests such as the traditional or modified 505, the L-drill and the 45° sidestep. Examples of sport-specific measures are recording body positions and sprint time of an American football linebacker executing a 45° drop-back for curl-to-flat responsibility, or that of a badminton athlete executing multidirectional sprints from backhand rear court to forehand front court. Regarding training, it is appropriate to include strength and jump training with strength training prioritized to develop a foundation for unloaded and loaded jump training. Training to enhance COD capabilities should likely be incorporated during the phase where jump training is emphasized, and feature a progression from fundamental athletic maneuvers and sport-specific tasks observed during competition in the sport. Fundamental maneuvers include backpedaling, curvilinear sprinting, shuffling and multidirectional jumping. The progression to sport-specific training should include combining and sequencing maneuvers in a manner that replicates tasks executed at the respective position.